Violent encounters: a criminal event analysis of lethal and nonlethal outcomes - Weaver, Gregory (Journal of contemporary criminal justice, 2004)
This study identifies key factors from the criminal events perspective that affect the lethality of violent encounters. Data for this research are derived from the National Incident-Based Reporting System of the FBI. Using logistic regression analysis, the effects of several contextual factors, including weapon, location, time of incident, circumstances, and victim and offender characteristics and relationships are explored. Analysis reveals that variables from each of the six categories affect the lethality of interpersonal violence, but the circumstance and type of weapon exert the strongest influence. Our investigation demonstrates the utility of the criminal events perspective for explaining the outcomes of violent encounters.